Pengaruh Karakteristik Wirausaha dan Lingkungan Eksternal pada Keberhasilan Usaha di Era Pandemi Covid-19 - Zega, Erwin Putra Rahmat Jaya; Indrawati, Henny; Asmit, Brilliant (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2023)
The purpose of this study was to determine the effect of entrepreneurial characteristics and the external environment on the success of the Tampan District makanan ringan micro business in the era of the COVID-19 pandemic. MSMEs, especially micro businesses, are threatened with closure due to the COVID-19 pandemic which has not only damaged the health sector but the Indonesian and even the world's economic sector. This research was conducted on 71 makanan ringan micro entrepreneurs in Tampan District with quantitative research methods and analyzed using descriptive analysis, Multiple Linear Regression and Hypothesis Testing. From this study, it was found that entrepreneurial characteristics and the external environment had a positive effect on the success of the Tampan District makanan ringan micro business in the era of the COVID-19 pandemic.